Updating of the detector system applied to the customs inspection systems based on electron accelerators - Gavrish, Yu.N.; Novikov, V.L.; Sidorov, A.V.; Fialkovsky, A.M. (Вопросы атомной науки и техники, 2006)
The updating of the detector systems developed at NPK LUTS for application to customs inspection systems based on 6…10 MeV accelerators is considered. Tests of a new updated detector system applied in an industrial introscope based on a 15 MeV accelerator have demonstrated a wider range of thickness of scanned (from 100…360 to 75…410 mm) objects at a resolution of 1-1T according to the radiographic ASTM standard.